Pendampingan Pemahaman Konsep Matematika Pada Siswa Sekolah Menengah Di Kampung Kadumula - Dini Delini; Ira Asyura; Linda Linda; Usep Saepul Mustakim; Devaron Suardi (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2022)
Learning assistance during the COVID-19 pandemic is a service to the community, as one of the efforts to implement the Tridharma of University. The implementation of learning carried out by the school during the COVID-19 pandemic uses online or online methods through whatApp groups, google meet and zoom. However, most students complained that they did not understand during the learning process. Especially in mathematics. Where in a long period of time, some students at school think that mathematics is a difficult subject. This subject is a frightening specter for students in most schools. Not only in Kadumula village, but in various regions throughout Indonesia. For this reason, various efforts need to be made to overcome the problem of learning difficulties. Therefore, the authors held mentoring activities for understanding mathematical concepts for high school students. The learning mentoring method used is to provide offline learning assistance, namely students and students carry out the learning and teaching process directly and face to face. This learning assistance is carried out in small groups consisting of 3-6 people. Study assistance is located in the home of one of the students. The stages of mentoring implementation are 1) problem observation, 2) activity planning, 3) activity schedule preparation 4) mentoring implementation, 5) evaluation stage.